2019
DOI: 10.1080/19476337.2019.1630484
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of rheological properties of cloudy apple juice using master curve

Abstract: The effect of temperature and concentration on the rheological behavior of pasteurized apple juice has been studied using a rotational rheometer at shear rates ranging from 0.5 to 12 s −1. The rheological properties were measured at different conditions changing from 10°C to 60°C and from 15°Brix to 40°Brix. On the basis of the obtained results, flow curves were prepared and consistency coefficients and flow indexes were determined. The superposition technique was applied to model behavior of apple juice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(41 reference statements)
0
9
0
4
Order By: Relevance
“…Polysaccharides including starch are mainly responsible for the turbidity of juices. Starch also resulted in slowing down the filtration rate, membrane fouling, gel formation in concentrated solutions and haziness [15]. Therefore, destarching is an essential step for juice clarification.…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides including starch are mainly responsible for the turbidity of juices. Starch also resulted in slowing down the filtration rate, membrane fouling, gel formation in concentrated solutions and haziness [15]. Therefore, destarching is an essential step for juice clarification.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the power law model can be chosen as the best-fitted model for describing the rheological characteristics of mulberry puree. Several studies have reported that the power law model was the best-fitted model for rheological behaviors of cloudy apple juice [Kobus et al, 2019], malbec grape juice concentrates [Evangelista et al, 2020], and orange pulp [Payne & Reyes-de-Corcuera, 2021].…”
Section: Results and Discussion The Electrical Conductivity Of Mulberry Pureementioning
confidence: 99%
“…Nevertheless, there was a decreasing tendency of flow behavior index as the temperature increased with the most noticeable effect in the fresh puree. The independence of flow behavior index on temperature was also shown for guava juice concentrates [Abdullah et al, 2018], grape juice [de Castilhos et al, 2018], and cloudy apple juice [Kobus et al, 2019]. Findings from studies reporting the effect of ohmic heating on rheological behaviors of fruit products varied.…”
Section: The Effect Of Processing Conditions and Temperature On Rheological Characteristics Of Mulberry Pureementioning
confidence: 96%
See 2 more Smart Citations